Does the cognitive activity can generate student’s physics argumentation performance features? - Viyanti, Viyanti; Cari, Cari; Prasetyo, Zuhdan Kun; Maulina, Hervin (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
A performance feature is a domain-specific to the organization of knowledge. Well-organized knowledge is characterized when students are able to collaborate the knowledge features of the physics problem.  The knowledge feature can be a cognitive activity where teachers influence students by changing the pattern of knowledge from "defining" to "applying" knowledge. This research aims to analyze whethet the cognitive activity from the teacher can generate student’s argumentation performance features or no. This study is a qualitative descriptive study which involved 100 of high school students in Bandar Lampung.   The data  was collected using a research instrument in the form of reasoned multiple choices which has been validated.  The results of this study showed that students' involvement in cognitive activity by following variety of procedures can generate student’s argumentation performance fetaures.